Thickness measurement of thick metallic plates by an eddy current multi-sensor system - Nebair, Hocine; Cheriet, Ahmed; Helifa, Bachir (Université de Laghouat , Bibliothèque centrale, 2017)
When an inductive sensor traversed by an AC current is approached to a metal part, variable electric currents, called eddy currents, appear in this part. These eddy currents, depending on their distribution in the part in question, produce a variation in the impedance of the sensor. Depending on the application, measuring and analyzing this impedance variation can be used to detect faults, electromagnetic characterization of the part or identify the geometrical properties of the part. Indeed, several characteristic quantities of the part which are at the origin of the variation of the impedance of the sensor. These quantities are the electrical conductivity of the part, its magnetic permeability and the dimensions of the part (thickness, etc.). It is known that the thickness measurement by eddy currents is limited to a certain characteristic thickness because of the penetration thickness; the intensity of the eddy currents decreases with the depth below the surface according to an exponential law. In this project, we propose a multi-sensor system with an eddy current dedicated to the measurement of thickness exceeding this characteristic thickness.